KEKUATAN MENGIKAT ISI DARI PERJANJIAN BAKU (STANDARD CONTRACT ) BAGI PARA PIHAK YANG MEMBUATNYA - Bustomi, Abuyazid (Solusi, 2017)
The purpose of this study is to describe and analyze the obedience of a standard contractual agreement for the parties that make it. The treaty constitutes an act whereby one or more persons commit themselves to one or more persons, in which case the legal standing between the parties to the treaty is the same and balanced. The agreement pursuant to the conception of article 1313 of the Civil Code, only mentions the party that binds itself to the other without determining what purpose the agreement is made. The treaty may be interpreted as an agreement by which two or more mutually excelent persons execute one thing in the field of property. This paper examines how the power of law and the consequences of standard / standard contract law for both parties in terms of freedom of contact. This writing is a normative juridical research. In general, the legal consequences of a treaty generally include a standard agreement, if it has fulfilled the terms of the terms of the validity of an agreement, then the agreement agreed and signed by the parties will be valid as a law for those who are bound and enter into the agreement. If the party bound in the agreement, unable to perform the performance or one of the parties to default, then the party who feels aggrieved may submit an objection to the party to perform the fulfillment of achievement, but if not ignored, then the party who feels aggrieved can do lawsuit Civil to the local District Court or the courts agreed upon and contained in the standard agreement.